Controladoria: avaliação das informações geradas pela controladoria na empresa X. - Sänger, Luana Thaís (Universidade do Vale do Rio dos Sinos, 2018)
The high competitiveness of the market makes the process of decision-making more complex within a company. It is indispensable that managers make as few mistakes as possible in their decision-making so that the company stays in balance and can be competitive. Having adequate information to support decision-making has reduce the susceptibility to mistakes. In the middle of this competitive market is Company X, which is an industry located in Vale dos Sinos founded, seventeen years ago, that realized the need to have economic-financial information to improve its business management. The purpose of this study is to analyze whether the Company X's controller is generating economic-financial information adequate to support decision-making. The research was developed by the descriptive method with qualitative approach. For data collection, we used document analysis, direct observation and interviews. After analyzing the results, it can be concluded that the economic-financial information that Company X's controller generates is extremely important to support managers' decision-making, and improvements are recommended to make them even more adequate.
Keywords: Controladoria; Informações econômico-financeiras; Tomadas de decisão; Controllership; Economic-financial information; Decision-making